2014
DOI: 10.1007/s00122-014-2285-z
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of LrSV2, a race-specific adult plant leaf rust resistance gene on wheat chromosome 3BS

Abstract: Fine mapping permits the precise positioning of genes within chromosomes, prerequisite for positional cloning that will allow its rational use and the study of the underlying molecular action mechanism. Three leaf rust resistance genes were identified in the durable leaf rust resistant Argentinean wheat variety Sinvalocho MA: the seedling resistance gene Lr3 on distal 6BL and two adult plant resistance genes, LrSV1 and LrSV2, on chromosomes 2DS and 3BS, respectively. To develop a high-resolution genetic map fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
0
13
0
3
Order By: Relevance
“…Insertion site‐based polymorphism markers have already been developed from BESs to anchor gene poor chromosome regions (Lucas et al, 2012); apart from this purpose, the ISBPs derived from minimum tiling paths are supposed to be evenly located along the chromosome arms, so they may be also of great value to assist the map‐based cloning of agronomically important genes. Also the SSRs developed from BES have been very useful in fine‐mapping projects in common wheat (Diéguez et al, 2014). The BESs were employed in the present work (i) to develop a new version of 5A GZ, anchoring contigs (in which the BESs are included) to the Brachypodium reference zipper and (ii) for anchoring contigs (developed with FPC and LTC assemblies) to the Illumina sequence contigs obtained from the IWGSC CSS, as detailed below.…”
Section: Resultsmentioning
confidence: 99%
“…Insertion site‐based polymorphism markers have already been developed from BESs to anchor gene poor chromosome regions (Lucas et al, 2012); apart from this purpose, the ISBPs derived from minimum tiling paths are supposed to be evenly located along the chromosome arms, so they may be also of great value to assist the map‐based cloning of agronomically important genes. Also the SSRs developed from BES have been very useful in fine‐mapping projects in common wheat (Diéguez et al, 2014). The BESs were employed in the present work (i) to develop a new version of 5A GZ, anchoring contigs (in which the BESs are included) to the Brachypodium reference zipper and (ii) for anchoring contigs (developed with FPC and LTC assemblies) to the Illumina sequence contigs obtained from the IWGSC CSS, as detailed below.…”
Section: Resultsmentioning
confidence: 99%
“…triticina ), Pm13 to powdery mildew (caused by Blumeria graminis f. sp. tritici ), Fhb1 to Fusarium head blight (caused by Fusarium graminearum Schwabe), and Wsm2 to WSMV (Mago et al, 2011; Hao et al, 2012; Lu et al, 2012; Diéguez et al, 2014; Liu et al, 2014). Research has shown that a higher number of gene loci are on the B genome compared with A and D genomes (IWGSC).…”
Section: Discussionmentioning
confidence: 99%
“…Even if Lr27 + Lr31 were present in the RIL population, these would not have provided effective resistance in the field tests at St. Paul. Diéguez et al (2014) identified an adult plant leaf rust resistance gene on chromosome 3BS with a hypersensitive resistance response, designated as LrSV2. LrSV2 cosegregated with cfb5006 that mapped closest to the 3BS QTL derived from Caldwell.…”
Section: Resultsmentioning
confidence: 99%